Social Economy and its relationship with the Industry 4.0. A study in Guanajuato’s SMEs - Arredondo-Hidalgo, María Guadalupe; Caldera-González, Diana del Consuelo (Technium Social Sciences Journal, 2022)
The objective of this research paper is to determine the degree of relationship between the emergent technologies and the industry 4.0, and the Social and Solidarity-based Economic model. The research paper is a product of a quantitative analysis in 62 Guanajuato state’s (Mexico) SMEs. The results show that there is a correlation between economy 4.0 and social economy. Therefore, it is necessary to create the required conditions to display the Industry 4.0 within the fabrication process, in which the following aspects are found: the development of national strategies, which lead the coordinate display of Industry 4.0; the creation of a multilateral mechanism, in which the interested parts institutionalize a participative scope in order to promote Industry 4.0; the creation of international cooperation mechanisms to accelerate the transfer of technology and technical knowledge.